A comparison of the parental values of children’s extracurricular music learning in Guilin, China and in Tampa, United States - Cui, Cancan; Xie, Xin (Frontiers in Psychology, 2024)
Many parents enroll their children in extracurricular music activities. However, cultural differences may contribute to parents’ different values that ultimately influence their behaviors and attitudes. This cross-cultural study aimed to compare the value parents have on their children’s private music education by examining four cases in Guilin, Guangxi (China) and Tampa, Florida (United States). Two main research questions guided this study: (1) How do parents in Guilin and Tampa perceive and value their children’s music learning? (2) Does the value parents hold for their children’s extracurricular music activities differ across different cultural contexts? If so, how do parents’ values and perceptions of their children’s involvement in extracurricular music activities differ between the contexts of Guilin and Tampa? We purposefully selected participants from two regions based on these criteria: (a) the participants included a single-child family and a two-child family in each of the two regions; (b) children’s age ranged from 5 to 12 years and lived with their biological parents (c) children were currently taking music lessons after school. We interviewed both children and parents during the data collection. The key findings reveal that parental values transcend two cultural contexts, specifically in (1) motivations for music learning, (2) expectations of music learning, (3) utilizing personal background, and (4) strategies for success. The findings suggest that several factors, such as children’s autonomy, musical joy, pursuit of musical career, “beauty development” and achievements, may have contributed to parents’ values. The implication for parents, psychologists, and policymakers is to understand the diverse needs and values within different cultural backgrounds, to promote the children’s development, to design curricula, and to use effective teaching methods in music education. In conclusion, both Guilin’s and Tampa’s parents’ values varied due to cultural differences, which further influenced their behaviors, attitudes and perceptions toward their children’s musical experiences.